2017
DOI: 10.21670/ref.2017.35.a7
|View full text |Cite
|
Sign up to set email alerts
|

Fronteras europeas: De lo histórico a lo cotidiano

Abstract: El presente artículo reflexiona sobre fronteras europeas y sus dinámicas cotidianas desde una óptica transfronteriza. Se parte de algunos hechos recientes que cuestionan la actual política de fronteras de la Unión Europea para hacer a continuación un repaso de la literatura sobre fronteras y territorios fronterizos. Posteriormente, se discuten los aspectos cotidianos que las prácticas transfronterizas tienen para los habitantes de los espacios fronterizos. En algunas ocasiones, y para completar el cuadro, se h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Some of the studies pay attention to difficulties in conducting border diplomacy (Thontowi, 2011;Puddu, 2017;Bautista et al, 2017), and the important role of state in conducting border diplomacy (Rachmawati & Fauzan, 2012;Perwita & Meilisa, 2018). Other research found that local people play an important role as an actor in daily border activities and interactions: shopping, fishing, or visiting and they take advantages from those activities (Musyaqqat, 2019;Bassols & Correa, 2017). But these last studies did not describe how various actors at the grassroots level create the dynamics of border management that in turn implicate the unique and harmonious interaction between people of two countries in the border area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the studies pay attention to difficulties in conducting border diplomacy (Thontowi, 2011;Puddu, 2017;Bautista et al, 2017), and the important role of state in conducting border diplomacy (Rachmawati & Fauzan, 2012;Perwita & Meilisa, 2018). Other research found that local people play an important role as an actor in daily border activities and interactions: shopping, fishing, or visiting and they take advantages from those activities (Musyaqqat, 2019;Bassols & Correa, 2017). But these last studies did not describe how various actors at the grassroots level create the dynamics of border management that in turn implicate the unique and harmonious interaction between people of two countries in the border area.…”
Section: Literature Reviewmentioning
confidence: 99%